Multimodal therapy including robot‐assisted radical cystoprostatectomy for locally advanced prostate cancer with bladder and ureteral invasion: A case report. Issue 5 (29th June 2022) - Okumi, Masayoshi; Kujime, Yuma; Matsumura, Soichi; Kitakaze, Hiroaki; Nakano, Kosuke; Hongo, Sachiko; Yoshioka, Iwao; Takada, Shingo
Abstract : Introduction: It remains unclear whether robot‐assisted radical cystoprostatectomy for locally advanced prostate cancer represents excessive treatment. Case presentation: A 58‐year‐old man presented with urinary retention and renal failure. Prostate‐specific antigen level was 38.07 ng/mL and computed tomography scans revealed bilateral hydronephrosis due to prostate enlargement. Prostate biopsy revealed a Gleason score of 5 + 5 adenocarcinoma, and bilateral hydronephrosis persisted even after urethral catheter placement. We diagnosed locally advanced prostate cancer with bladder and ureteral invasion. Percutaneous bilateral nephrostomy was performed, and neoadjuvant hormone therapy was initiated. Four months after the start of hormone therapy, robot‐assisted radical cystoprostatectomy and an intracorporeal ileal conduit were performed, followed by adjuvant radiation therapy for lymph node metastasis. Seven months after the surgery, the patient was free of disease with prostate‐specific antigen level <0.03 ng/mL. Conclusion: Robot‐assisted radical cystoprostatectomy can be an effective multimodal therapy for locally advanced prostate cancer with bladder and ureteral invasion by locally advanced prostate cancer.